2017
DOI: 10.1371/journal.pone.0168277
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Ovarian Metastases in Breast Cancer Patients < 41 Years of Age in the Netherlands: A Nationwide Retrospective Cohort Study

Abstract: PurposeBreast cancer is one of the primary indications for cryopreservation and subsequent autotransplantation of ovarian tissue. The safety of this fertility preservation method remains questionable, as the presence of disseminated breast tumor cells cannot yet be excluded in the ovarian autografts. We explored the prevalence of ovarian metastases among young breast cancer patients and determined risk factors for the development of ovarian metastases.MethodsUsing the nationwide database of the Dutch Pathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…stated that lobular BCs are more likely to metastasize to the ovary than ductal BCs; however, Peters et al . did not observe any significant differences in histological subtypes of BCs that metastasize to the ovaries 6,24 . In our study, 6 women had breast carcinoma metastases to ovary and the subtype was lobular carcinoma in 3 of them.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…stated that lobular BCs are more likely to metastasize to the ovary than ductal BCs; however, Peters et al . did not observe any significant differences in histological subtypes of BCs that metastasize to the ovaries 6,24 . In our study, 6 women had breast carcinoma metastases to ovary and the subtype was lobular carcinoma in 3 of them.…”
Section: Discussioncontrasting
confidence: 52%
“…Adnexal masses are frequently seen in BC patients. Ovarian involvement is the most common one in female genital tract metastases, the incidence of ovarian metastases in BC patients is 13–47%, which was demonstrated by the methods of autopsies as well as prophylactic and therapeutic oophorectomies 4–6 …”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the primary tumor could not be identified in 15% of OM cases (17). The incidence of OM in patients with breast cancer ranges between 13 and 47% (these percentages are mainly based on autopsies or prophylactic or therapeutic oophorectomies) (18)(19)(20). OM from breast cancer is mainly found after surgery at the primary site.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies suggest that up to 50% of ovarian metastases are bilateral. [5,6,15,16] Moreover, MRI has high accuracy for differentiating benign and malignant ovarian tumors. [17] Regarding serum markers, patients with metastases showed lower levels of serum CA125 (<80 U/mL), higher levels of serum CA153 (>100 U/mL), and lower BRCA mutation probability (<20%) than patients with primary ovarian tumors.…”
Section: Discussionmentioning
confidence: 99%